Implementation of The Program to Prevent Early Potential Social Conflicts in The Agency of National Unity and Politics of East Java Province - Hidayati, Gina Arini; Megawati, Suci; Rusli, Nashatul Afrina Binti (Journal of Social Dynamics and Governance, 2025)
This study aims to analyze the effectiveness of the implementation of the Early Prevention of Potential Social Conflict Program in East Java Province using the Van Meter and Van Horn Policy Implementation Model. The main focus of the study includes five key variables: policy standards and objectives, resources, inter-organizational communication, economic, social, political conditions, and the disposition of implementers. This research uses a qualitative approach through in-depth interviews, observations, and documentation studies on the East Java Bakesbangpol and conflict management support forums. Data analysis was carried out using Miles and Huberman’s interactive analysis technique. The results of the study show that normatively policy standards and objectives have been clearly formulated through a strong legal foundation; However, translation at the district/city level still varies, causing implementation gaps. Human resources and budgets are relatively adequate, but the competence and consistency of implementers are not evenly distributed. Communication mechanisms between organizations are formal but not fully effective due to information delays and sectoral egos. Social, economic, and political conditions in East Java are generally conducive, although there are vulnerable areas that demand a faster response. The willingness of the implementers shows a positive commitment, but the success of the program is greatly influenced by the attitude of regional leaders. Overall, policy implementation is going quite well, but it still requires strengthening coordination, standardizing policy understanding, and increasing implementation capacity. These findings are expected to be a reference for local governments in formulating strategies for handling social conflicts that are more adaptive, responsive, and based on multi-stakeholder collaboration